Mutual acoustic impedance of circular membranes and plates with bessel axially-symmetric vibration velocity distributions - RDZANEK, Witold (Archives of Acoustics, 1980)
In this paper the mutual impedance of circular membranes and circular plates clamped at the circumference is analyzed. It was assumed that a Bessel axially-symmetric vibration velocity distribution was predetermined on the surface of the sources, and that the sources were placed in a rigid planar baffle. The impedance was calculated by a method based on a Fourier representation of the acoustic pressure. In view of the axially-symmetric vibration velocity distribution, the acoustic pressure and the subsequent formulae for the mutual impedance are given in the Hankel representation. As a result, the mutual impedance can be expressed in the form of a single integral. Practically useful formulae are derived for specific cases. The results of the calculation are also shown graphically.